The effectiveness of contemporary children’s literature module in enhancing the upper primary school pupils’ vocabulary mastery - Dg Syuhada Nabilah Abdull Majid,; Azlina Abdul Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Contemporary Children’s Literature (CCL) is being used worldwide as an extended reading material especially in the teaching and learning of English. Back in 2004, the Curriculum Development Centre of Malaysia introduced the CCL module for upper Primary School pupils that covers all the basic skills in English such as listening, speaking, reading, writing, grammar, and vocabulary. Vocabulary plays an important role in the process of learning a language. The lack of vocabulary hinders the pupils from using the target language. Thus, this study aimed to investigate how the use of CCL modules can effectively enhance the upper primary school pupils’ vocabulary. Quantitative approach using mixedmethodology design employing the pre and post test as well as questionnaires were used in this study. A total number of 90 upper primary pupils in a primary school in Penampang district, Sabah, Malaysia were selected using purposive sampling. Then, the data were analysed using the descriptive analysis model and Statistical Package for the Social Sciences (SPSS). The main findings indicated the results from the pre-test and post test showed a significant difference where the pupils’ marks in the post-test were higher than the pre-test. Hence, the findings depicted that the use of CCL modules can enhance the pupils’ vocabulary effectively. Finally, based on the research findings, it is recommended to conduct further studies that focus on other language skills. Policy makers are encourage to establish a designated time for teaching Contemporary Children’s Literature based on these implications.